Electrospun nanofibrous meshes cultured with Wharton’s Jelly Stem Cell: an alternative for cartilage regeneration, without the need of growth factors - Silva, Marta Luísa Sousa Dias Alves (2017)
Many efforts are being directed worldwide to the treatment of OA-focal lesions. The majority of those efforts comprise either the refinement of surgical techniques or combinations of biomaterials with various autologous cells. Herein, we tested electrospun polycaprolactone (PCL) nanofibrous meshes for cartilage tissue engineering. For that, articular chondrocytes (hACs) isolated from human osteoarthritic joints and Whartonâ s Jelly Stem Cells (hWJSCs) are cultured on electrospun nanofiber meshes, without adding external growth factors. We observed higher glycosaminoglycans production and higher overexpression of cartilage-related genes from hWJSCs cultured with basal medium, when compared to hACs isolated from osteoarthritic joints. Moreover, the presence of sulfated proteoglycans and collagen type II is observed on both types of cell cultures. We believe that this effect is due to either the electrospun nanofibers topography or the intrinsic chondrogenic differentiation potential of hWJSCs. Therefore, we propose the electrospun nanofibrous scaffolds in combination with hWJSCs as a viable alternative to the commercial membranes used in autologous chondrogenic regeneration approaches.